"Oh, you have a 'she'?" : exploring the lived experiences of black same-sex females living in Grahamstown, South Africa - Haihambo, Naem Patemoshela (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
The South African Constitution prohibits discrimination on the basis of a variety of factors including race and gender and sexual orientation. This inclusion came in 1996 after an oppressive apartheid regime was overcome, also positioning the South African Constitution amongst the more liberal, especially in the wider African context. This inclusion and the contextual disparity has caused curiosity about the realities of same-sex sexualities, especially taking into consideration media reports on violence and perceived social opposition of same- sex sexualities in South Africa. Much of this attention has motivated research studies on same-sex sexualities. Within this research, however, black female same-sex sexualities have been positioned as vulnerable and victimised within the heteronormative context, with much of this research focusing on 'corrective/curative' rape. There has however been increasing efforts in moving away from this limiting position by a select few (e.g. Zanele Muholi and Zethu Matebeni) in a more explorative direction in attempts to investigate black female sexualities as complex and expressive rather than passive. This study is an interpretive phenomenological investigation of the lived experiences of black female same-sex sexualities and the plurality of identities that influence their everyday experiences. This took into account intersectionality, heteronormativity and queer theory, which provided a theoretical framework for this study. During the interview process, participants described their experiences as black same-sex females in a variety of contexts including their experiences and influences of external factors (such as family and university. From the results of this research, experiences and identities of participants are presented as complex, fluid, expressive and to some extent political. Participants also expressed the difficulties encountered with misinformed friends and families and describe ways in which they assert themselves within their social and personal contexts.
Keywords: Lesbians, Black -- South Africa -- Makhanda; Lesbians, Black -- South Africa -- Makhanda -- Psychology; Lesbians, Black -- South Africa -- Public opinion; Lesbianism -- South Africa -- Makhanda; Lesbianism -- South Africa -- Public opinion